Serum Vascular Endothelial Growth Factor Levels before and after Intravitreous Ranibizumab Injection for Retinopathy of Prematurity - Xuting Chen; Lin Zhou; Qi Zhang; Yu Xu; Peiquan Zhao; Hongping Xia (Journal of Ophthalmology)
Background. Retinopathy of prematurity (ROP) is one of the common complications of prematurity. Intravitreal injection of ranibizumab (IVR), an antivascular endothelial growth factor (VEGF) drug, showed significant benefit for ROP. However, there are concerns about systemic complications of anti-VEGF therapy in preterm infants. Objectives. To evaluate serum VEGF level in the systemic circulation after IVR and the complications associated with IVR for the premature infants with ROP. Methods. This prospective investigation assessed the serum concentrations of VEGF in ROP patients before and after IVR therapy. All the infants had binocular retinopathy and received IVR 0.25 mg per eye as the primary treatment. Serum samples were collected 1 day prior to injection and 1 day, 3 days, and 7 days after IVR treatment. Serum VEGF level was measured by the enzyme-linked immunosorbent assay (ELISA). Results. Fifteen infants (6 girls and 9 boys) were enrolled. The serum concentrations of VEGF 1 day before and 1 day, 3 days, and 7 days after a total of 0.5 mg intravitreal injections of ranibizumab were 226.9 (198.4, 272.4), 12.8 (7.0, 22.4), 16 (12.0, 20.8), and 33.7 (24.0, 48.0) pg/ml, respectively. Serum VEGF levels decreased significantly at 1 day, 3 days, and 7 days after IVR treatment compared with pretreatment concentration (P<0.05). Compared to days 1 and 3 after IVR, serum VEGF level at 7 days after IVR treatment increased significantly (P<0.05). Conclusion. Serum VEGF levels in patients with ROP were suppressed for at least 7 days after IVR treatment. Although the clinical significance of this phenomenon is uncertain, its safety profile requires further investigation.